Effects of paddy field non-grainization consolidation on sustainable eco-functions protection of soil bacterial: Empirical evidence from Zhejiang province, China - Liang, Ying; Geng, Bin (Frontiers in Environmental Science, 2023)
The increasing “non-grainization” of paddy fields affecting large-scale grain cultivation and impacting the sustainable eco-functions protection of soil bacterial in China. The same problem of “non-grainization” has threatened food security and farmland soil ecological functions in other areas of the world. Although previous research has demonstrated that soil microorganisms are strongly affected by land use change, little is known about the effects of paddy field non-grainization consolidation (NGC) on soil microorganisms. This study examined soil samples before and after paddy field NGC in Zhejiang province, China, measured soil environmental factors and performed 16S rDNA amplicon sequencing to analyze the changes in soilbacterial communities and ecosystem functions before and after NGC. Results show that NGC increased the relative abundances of Proteobacteria (27.89%) and Actinobacteria (25.25%) in the project zones. Total soil bacteria increased in all samples after NGC implementation in terms of absolute soil bacterial community content, but there were large differences. NGC improved the alpha diversity indices, including Ace, Chao1, Coverage, and Shannon indices (p < 0.01) in terms of soil bacterial community diversity. The data analysis of RDA and the significance test showed that the environmental factors which were close-knitted with the soil bacterial diversity and structure of the sample sites were TN, AP, pH, SOM, FIQ, and AK. Wilcoxon rank sum test results showed that NGC also significantly enhanced the amino acid transport and metabolic functions of soil bacterial. Our findings suggest that NGC is beneficial to improve the paddy field soil bacterial diversity, enhance the versatility of soil ecosystems, and promote sustainable arable land soil ecosystem protection. The quantitative results would be useful for better studying the use of land remediation engineering measures to the remediation and maintenance of bacterial diversity and sustainable eco-functions protection in paddy fields.